The English and empire digest : with complete and exhaustive annotations (London : Butterworth, 1919)
Intended to provide the whole case law of England, and a considerable body of cases from the courts of other countries of the British Commonwealth.
vol. 2 -- v. 3 -- v. 4 -- v. 5 -- v .6 -- v. 7 -- v.8 -- v. 10 -- v. 11-- v. 12 -- v.13 -- v. 14 -- v. 15 -- v.16 -- v.17 -- v. 18 --v. 19 -- v. 20 -- v. 21 -- v. 22 -- v. 23 -- v. 24 -- v. 25 -- v.26 -- v. 27 -- v. 28 -- v. 29 -- v. 30 -- v.31 -- v. 33 -- v. 34 -- v. 36 -- v. 37 -- v.38 -- v.39 -- v. 40 -- v. 41 -- v. 42 -- v. 43 -- v. 44 -- v.45 -- v.l 46 -- v.47 -- v. 48 --
Blue-band volumes replaced original edition.
Blue-band replacement volumes superseded by Green-band reissue volumes.
Supplemented by: Annual cumulative supplements and Continuation volumes.
Green-band reissue volumes not published in chronological order.
Keywords: Law reports, digests, etc. -- Great Britain; Court rules -- Great Britain -- Periodicals; Civil procedure -- Great Britain -- Periodicals